(untitled) (Journal of Partial Differential Equations, 2023)
In this paper, we mainly investigate the initial boundary value problem for a plate equation with non-local degenerate energy damping term and source term. By using potential well and Nakao’s inequality, we establish the global existence and the energy decay rate when the initial data is starting in the stable set. Finally, we derive some further estimate on the stability.